Obstructive jaundice secondary to bile duct involvement with Hodgkin’s disease: a case report - Sena, Veruska Di; Thuler, Fernanda Prata Borges Martins; Macedo, Erika Pereira; Paulo, Gustavo Andrade de; Libera, Ermelindo Della; Ferrari, Angelo Paulo (São Paulo Medical Journal, 2005)
CONTEXT: Obstructive jaundice due to lymphoma is very rare. It may be difﬁcult to distinguish between this condition and a large number of causes of extrahepatic bile duct obstruction, even by endoscopic retrograde cholangiography. Its prognosis is poor. Combined chemotherapy and/or radiotherapy with bile duct drainage is a therapeutic option. CASE REPORT: We describe a case of obstructive jaundice as the initial presentation of Hodgkin’s disease. After chemotherapy and endoscopic bile duct stenting, it was noted that the enlarged lymph nodes, jaundice and bile duct dilation disappeared.